Current Concepts in Intra-articular Calcaneus Fractures - Sposeto, Rafael Barban; Matías-Joannas, Germán; Godoy-Santos, Alexandre Leme (Revista brasileira de ortopedia, 2025)
Intra-articular calcaneal fractures are significant injuries to the locomotor system, often leading to lifelong impairments in foot mechanics with substantial occupational, social, and financial repercussions. The initial imaging diagnosis relies on radiography; however, computed tomography is crucial for understanding the three-dimensional anatomy of the fracture and facilitating surgical planning.The treatment of intra-articular calcaneal fractures remains a subject of debate, with literature supporting diverse approaches for similar fracture types. Currently, the gold standard for managing subtalar joint fractures is surgical intervention. Among the two most common techniques, the extended lateral and the sinus tarsi approaches yield comparable functional outcomes, though the latter is associated with fewer complications.The present article discusses the diagnosis, classification, and treatment of intra-articular calcaneal fractures, focusing on the sinus tarsi and extended lateral "L" approaches, as well as the fixation techniques applicable to each fracture type.